2012
DOI: 10.1179/1743290111y.0000000007
|View full text |Cite
|
Sign up to set email alerts
|

Study of high temperature wetting and infiltration for optimising liquid phase sintering in low alloy steels

Abstract: Liquid phase sintering is commonly used in powder metallurgy to improve physical properties through densification enhancement. With the aim of combining the advantages of liquid phase sintering and the use of promising alloying elements such as Mn and Si, liquid promoters with complex compositions were designed to provide a low melting point to form a liquid phase below the common sintering temperatures. The properties of these liquid phases were characterised in terms of contact angle, spreading evolution and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 31 publications
(62 reference statements)
2
30
0
Order By: Relevance
“…channels in the surrounding of the master alloy particles [22,32], favoring the formation of a micro-climate inside the secondary pore left by the master alloy particle. The liquid master alloy continuously changes its composition due to the diffusion of alloying elements and the dissolution of the iron base particles.…”
Section: Model For Microstructure Development and The Oxide Distributmentioning
confidence: 99%
“…channels in the surrounding of the master alloy particles [22,32], favoring the formation of a micro-climate inside the secondary pore left by the master alloy particle. The liquid master alloy continuously changes its composition due to the diffusion of alloying elements and the dissolution of the iron base particles.…”
Section: Model For Microstructure Development and The Oxide Distributmentioning
confidence: 99%
“…Figure A represents the evolution of the contact angle during the wetting experiments, while Figure B and C corresponds to the liquid‐solid interface on Fe and Fe‐C substrates, respectively. Due to the absence of a specific melting point, the progressive melting of the alloy within a temperature range makes the wetting calculations even more complicated, since it is not easy to separate the first stages of spreading from the melting process itself …”
Section: Resultsmentioning
confidence: 99%
“…The wettability of the master alloy Fe-Mn-Si-C on plain iron substrates under N 2 -10H 2 atmosphere was reported in previous studies and compared with the wettability of Cu on the same type of substrates but under Ar atmosphere 15,16 . In those studies, the wetting angle provided by the master alloy was reported to be around 20º, while that of Cu was approximately 70º.…”
Section: Bwetting Experimentsmentioning
confidence: 99%
“…This evolution of the wetting angle is due to the dissolution of the iron oxide layer by the liquid master alloy. The ability of this master alloy to dissolve the iron substrate is due to the chemical compatibility between the iron substrate and the liquid formed 16 . The conditions used for the wetting experiments performed represent the worst case scenario where no reducing agents are available.…”
Section: Bwetting Experimentsmentioning
confidence: 99%
See 1 more Smart Citation